2002
DOI: 10.1002/qj.200212858304
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation effects on the habit of vapour grown ice crystals from −18 to −42°C

Abstract: SUMMARYIce crystals have been nucleated and grown by a new method where supersaturation is controlled by combining static diffusion chamber and expansion chamber techniques. Crystals were nucleated and grown on 50 µm diameter glass filaments at pressures of 500 to 300 hPa, typical of clouds with temperatures from −18 to −42 • C, respectively. Crystals were also nucleated on particles of finely powdered silver iodide and kaolinite adhering to glass filaments, in order to investigate effects on habit due to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 34 publications
7
55
1
Order By: Relevance
“…Several earlier studies (Mason and Maybank, 1958;Roberts and Hallett, 1968;Shaller and Fukuta, 1979;Bailey and Hallett, 2002) demonstrated that the threshold temperature for ice nucleation by deposition freezing on kaolinite is about 253 K. For immersion mode freezing, an onset temperature of 259 K has been reported (Pitter and Pruppacher, 1973). The results presented here confirm that contact freezing is the most efficient ice nucleation process involving kaolinite particles, with freezing temperatures being observed up to 267 K. In previous work Pitter and Pruppacher (1973) studied contact freezing of water drops with kaolinite and montmorillonite particles.…”
Section: Discussionsupporting
confidence: 77%
“…Several earlier studies (Mason and Maybank, 1958;Roberts and Hallett, 1968;Shaller and Fukuta, 1979;Bailey and Hallett, 2002) demonstrated that the threshold temperature for ice nucleation by deposition freezing on kaolinite is about 253 K. For immersion mode freezing, an onset temperature of 259 K has been reported (Pitter and Pruppacher, 1973). The results presented here confirm that contact freezing is the most efficient ice nucleation process involving kaolinite particles, with freezing temperatures being observed up to 267 K. In previous work Pitter and Pruppacher (1973) studied contact freezing of water drops with kaolinite and montmorillonite particles.…”
Section: Discussionsupporting
confidence: 77%
“…Following this, the concentrations fell back to the background levels and then eventually rose again, increasing the activated fraction to just below the 8% threshold while the humidity remained close to or at water saturation. This result seems anomalous but it may indicate that deposition nucleation is occurring at these relatively warm temperatures, as found by Roberts and Hallett (1968) and Bailey and Hallett (2002). This difference may be compositional, size related or a result of low nucleation efficiencies (<0.5% of the dust sample) that mean we are not able to observe the ice produced via deposition at these temperatures with the SID.…”
Section: Discussionmentioning
confidence: 68%
“…They found that kaolinite particles that had previously formed ice crystals now activated at 10% supersaturation with respect to ice, suggesting that ageing could produce more efficient ice nuclei. More recently, Bailey and Hallett (2002) have nucleated ice on glass filaments coated with kaolinite at temperatures up to −12 • C and 12% supersaturation with respect to ice. In contrast, Salam et al (2006) used commercially available mineral dust particles and found that warmest temperature at which kaolinite particles with a mean diameter of 1 µm formed ice was −22 • C and 23% supersaturation with respect to ice, which is very close to water saturation.…”
Section: Introductionmentioning
confidence: 99%
“…Since initial work that identified crystal shapes using in situ ob-servations of ice clouds (e.g., Weickmann, 1948, and studies summarized by Dowling and Radke, 1990, and by Heymsfield and McFarquhar, 2002), much effort has been devoted to quantify the microphysical and scattering properties of ice crystals. One important finding is that ambient atmospheric conditions (e.g., temperature and humidity) govern the growth and morphological properties of ice crystals (e.g., aufm Kampe et al, 1951;Lamb and Scott, 1974;Gonda, 1980;Fukuta and Takahashi, 1999;Bacon et al, 2003;Bailey and Hallett, 2002, 2012Korolev et al, 2004) upon which the corresponding scattering properties depend (e.g., Takano and Liou, 1995;Macke et al, 1996;Yang and Liou, 1998;Baran et al, 2001Baran et al, , 2005Yang et al, 2005Yang et al, , 2013Um and McFarquhar, 2007.…”
Section: Introductionmentioning
confidence: 99%